Preparation method of high-hardness low-roughness micro-arc oxidation film of annular aluminum piece

By performing two-step microarc oxidation treatment on the annular aluminum parts, using the first and second solutions of specific compositions, the problems of uneven thickness, low hardness and high roughness of the inner and outer surface film layers of the annular aluminum alloy parts in the prior art are solved, and a microarc oxidation film with high hardness and low roughness are realized, and the use performance is improved.

CN119530921APending Publication Date: 2025-02-28CHONGQING SCI & INNOVATION CENT OF NORTHWEST POLYTECHNICAL UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411788877.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

After the existing micro-arc oxidation treatment, the thickness of the inner and outer surface film layers of the annular aluminum alloy parts is uneven, and the formed micro-arc oxidation film has low hardness and excessive roughness, which seriously affects the performance of the annular aluminum alloy parts.

Method used

By immersing the annular aluminum parts in the first solution and the second solution in sequence for microarc oxidation treatment, the first solution contains phosphate, silicate, EDTA salt, hydroxide and tartrate, and the second solution contains hexametaphosphate, silicate, fluorine salt, EDTA salt, hydroxide and citrate, and two microarc oxidation treatments are used to form a uniform microarc oxidation film.

Benefits of technology

The uniformity of the micro-arc oxide film on the inner and outer surfaces of the annular aluminum parts is achieved, the hardness of the film is improved, and the roughness is reduced, and the performance of the annular aluminum alloy parts is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-hardness and low-roughness micro-arc oxidation film of an annular aluminum part, relates to the technical field of surface treatment, and aims to solve the technical problems that the thicknesses of film layers on the inner surface and the outer surface of the annular aluminum part subjected to existing micro-arc oxidation treatment are not uniform, and the formed micro-arc oxidation film is low in hardness and too large in roughness. The preparation method of the micro-arc oxidation film comprises the steps that after an annular aluminum piece is sequentially immersed in a first solution and a second solution, the annular aluminum piece is taken out and dried, and the micro-arc oxidation film is formed on the surface of the annular aluminum piece; wherein the first solution comprises phosphate, silicate, EDTA (Ethylene Diamine Tetraacetic Acid) salt, hydroxide and tartrate; the second solution comprises hexametaphosphate, silicate, villiaumite, EDTA (Ethylene Diamine Tetraacetic Acid) salt, hydroxide and citrate. According to the technical scheme, the preparation method of the high-hardness and low-roughness micro-arc oxidation film of the annular aluminum part and the micro-arc oxidation film prepared through the preparation method are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface treatment, and more specifically to a method for preparing a micro-arc oxidation film with high hardness and low roughness for an annular aluminum part. Background Art

[0002] Aluminum alloys are lightweight and high-strength, and are relatively inexpensive. They are widely used in daily life, industrial production, national defense and military, and are one of the most important metal materials. Aluminum alloys also have the common shortcomings of light alloys. They have low hardness and poor friction and wear resistance, so they need surface enhancement when used in rotating parts. Micro-arc oxidation is an electrochemical conversion film technology that can generate oxide ceramic films by treating metals such as magnesium, aluminum, and titanium, greatly improving the surface hardness, wear resistance, and corrosion resistance of the material. It has the advantages of low cost and good environmental protection, and is one of the most commonly used technical means to solve the problem of surface wear resistance of aluminum alloy parts.

[0003] One of the rules of conventional micro-arc oxidation treatment is that with the increase of treatment time and voltage, the thickness, hardness and roughness of the ceramic film gradually increase. For annular aluminum alloy parts, affected by the charge skin effect, the growth rate of the film layer on the outer surface is much higher than that on the inner surface during the micro-arc oxidation process, resulting in uneven thickness of the inner and outer surfaces, and the micro-arc oxidation film formed has low hardness and excessive roughness, which seriously affects the performance of the annular aluminum alloy parts. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a micro-arc oxidation film with high hardness and low roughness for an annular aluminum part, which is used to solve the technical problems that the film thickness of the inner and outer surfaces of the annular aluminum alloy part after the existing micro-arc oxidation treatment is uneven, and the formed micro-arc oxidation film has low hardness and excessive roughness, which seriously affects the performance of the annular aluminum alloy part. The annular aluminum part in this application is an annular aluminum alloy part. In view of this, the present invention is implemented through the following scheme.

[0005] In a first aspect, the present invention provides a method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part, comprising: The annular aluminum piece is immersed in the first solution and the second solution in sequence, and then taken out and dried, so that a micro-arc oxidation film is formed on the surface of the annular aluminum piece; The first solution includes phosphate, silicate, EDTA salt, hydroxide and tartrate; the second solution includes hexametaphosphate, silicate, fluoride salt, EDTA salt, hydroxide and citrate.

[0006] Compared with the prior art, the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention is used to prepare a micro-arc oxidation film on the inner and outer surfaces of the annular aluminum part, and the annular aluminum part is immersed in a first solution and a second solution in turn for micro-arc oxidation treatment. The annular aluminum part is immersed in the first solution for the first micro-arc oxidation treatment, and a first micro-arc oxidation reaction occurs during the first micro-arc oxidation treatment. The annular aluminum part is immersed in the second solution for the second micro-arc oxidation treatment, and a second micro-arc oxidation reaction occurs during the second micro-arc oxidation treatment. Specifically, in the process of the first micro-arc oxidation treatment, phosphate and silicate are used as main salts in the first solution to enhance the passivation ability of the first solution on the annular aluminum part, and tartrate is used to exert the effect of the first solution. The invention has an antioxidant effect, and is used to inhibit the overly violent micro-arc oxidation reaction during the first micro-arc oxidation treatment, and by controlling the parameters of the first micro-arc oxidation treatment within a reasonable range, a barrier layer can be formed on the surface of the annular aluminum part; in the second micro-arc oxidation treatment, hexametaphosphate and silicate are used as main salts to promote the growth effect of the film (such as uniformity, reasonable growth rate), and fluoride salts and hydroxides (high concentration) are added to increase the conductivity of the second solution, which is further used to enhance the micro-arc oxidation reaction; further, the present invention adds citrate to the second solution, and the citrate plays a role in smoothing the oxide film during the second micro-arc oxidation treatment, so that the film layer can be rapidly thickened while inhibiting the increase or improvement of the roughness of the film layer.

[0007] It should be further explained that after the first micro-arc oxidation treatment, due to the strong passivation effect of the first solution, a high-density smooth micro-arc oxidation film can be quickly obtained on the surface of the annular aluminum part, but it is difficult to increase the thickness and hardness of the micro-arc oxidation film to the expected range. For this reason, the present invention selects a second solution with a strong ability to promote film growth during the second micro-arc oxidation treatment. After the second micro-arc oxidation treatment, the micro-arc oxidation film finally reaches the thickness requirement. The benefit is that in the first micro-arc oxidation treatment, the passivation layer (equivalent to the barrier layer, which plays a role in stimulating the second micro-arc oxidation reaction) is formed at a faster rate, and its density and smoothness are high; after the first micro-arc oxidation treatment, the passivation layer (or barrier layer) that has been formed on the surface of the annular aluminum part can directly stimulate the micro-arc oxidation reaction of the second micro-arc oxidation treatment. It is precisely because of the existence of the passivation layer that the uniformity of the second micro-arc oxidation reaction can be effectively improved, and the overall preparation time of the micro-arc oxidation film of the annular aluminum part can be shortened, which not only improves the preparation efficiency, but also ensures the high density and smoothness of the film layer (if the second micro-arc oxidation treatment is directly entered without the first micro-arc oxidation treatment, due to the weak passivation ability of the second solution, the passivation process will be slow, the treatment time will be greatly increased, and the roughness of the oxide film will increase and the density will decrease). Therefore, through the combined action (or mutual cooperation) of the first solution and the second solution, or in other words, through the combined action (or mutual cooperation) of the first micro-arc oxidation treatment and the second micro-arc oxidation treatment, the micro-arc oxidation film formed on the inner and outer surfaces of the annular aluminum part is maintained at a uniform level, and while the hardness of the micro-arc oxidation film is improved, the roughness of the micro-arc oxidation film can also be reduced, and a micro-arc oxidation film that meets the requirements is formed on the surface of the annular aluminum part. In summary, the above-mentioned technical solution of the present invention solves the technical problems that the thickness of the film layer on the inner and outer surfaces of the annular aluminum alloy part after the existing micro-arc oxidation treatment is uneven, and the formed micro-arc oxidation film has low hardness and excessive roughness, which seriously affects the performance of the annular aluminum alloy part.

[0008] Further, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention, the first solution includes, based on the amount of the first solution, 10 to 20 g / L of phosphate, 15 to 30 g / L of silicate, 3 to 8 g / L of EDTA salt, 0.5 to 3 g / L of hydroxide and 7 to 15 g / L of tartrate; and / or, In terms of the amount of the second solution, the second solution includes 15-25 g / L of hexametaphosphate, 15-30 g / L of silicate, 10-22 g / L of fluoride salt, 3-8 g / L of EDTA salt, 2-6 g / L of hydroxide and 5-10 g / L of citrate.

[0009] Furthermore, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention, the phosphate comprises trisodium phosphate and tripotassium phosphate; and / or, The silicate comprises sodium silicate and potassium silicate; and / or, The EDTA salt includes disodium EDTA and dipotassium EDTA; and / or, The hydroxide comprises sodium hydroxide and potassium hydroxide; and / or, The tartrate includes sodium tartrate, potassium tartrate and sodium potassium tartrate; and / or, The hexametaphosphate includes sodium hexametaphosphate; and / or, The fluoride salts include sodium fluoride and potassium fluoride; and / or, The citrate includes sodium citrate and potassium citrate.

[0010] Furthermore, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention, in the process of immersing the annular aluminum part in the first solution and the second solution in sequence, the temperature of the first solution and / or the second solution is 8~35°C.

[0011] Furthermore, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention, in the process of immersing the annular aluminum part in the first solution and the second solution in sequence, the current parameters of the first solution include: a frequency of 300-500 Hz, a duty cycle of 2.5-5%, and a current density of 1-2 A / dm 2 , the termination voltage is 420~480V, and the processing time is 8~15min; and / or, The current parameters of the second solution include: frequency of 500-1000 Hz, duty cycle of 4-12%, current density of 1.5-5 A / dm 2 , the termination voltage is 450~580V, and the processing time is 20~35min.

[0012] Furthermore, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention, in the process of immersing the annular aluminum part in the first solution and the second solution in sequence, the annular aluminum part is the anode, the stainless steel plate is the cathode, and an auxiliary cathode is provided.

[0013] Furthermore, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention, the auxiliary cathode comprises a stainless steel tube; and / or, During the process of immersing the annular aluminum member in the first solution and the second solution in sequence, the auxiliary cathode passes through the inner cavity of the annular aluminum member.

[0014] Furthermore, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part of the present invention, the diameter of the auxiliary cathode is less than or equal to 1 / 2 of the minimum diameter of the inner cavity of the annular aluminum part; and / or, The length of the auxiliary cathode is less than or equal to twice the axial length of the annular aluminum member.

[0015] Furthermore, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part of the present invention, the annular aluminum part is immersed in the first solution and the second solution in sequence, and then taken out and dried, comprising: Step 1, clamping the annular aluminum piece with a conductive hanger as an anode, the stainless steel plate as a cathode, passing the stainless steel tube through the inner cavity of the annular aluminum piece, and using the stainless steel tube as an auxiliary cathode; Step 2, immersing the annular aluminum part in the first solution and performing a first micro-arc oxidation treatment, wherein the first micro-arc oxidation treatment lasts for 8 to 15 minutes; Step 3, taking out the annular aluminum piece from the first solution and cleaning it with deionized water; Step 4, the annular aluminum piece is clamped with a conductive hanger as an anode, the stainless steel plate and the stainless steel tube are used as a cathode and an auxiliary cathode respectively, the annular aluminum piece is immersed in the second solution, and a second micro-arc oxidation treatment is performed, and the time of the second micro-arc oxidation treatment is 20 to 35 minutes; Step 5, taking out the annular aluminum piece from the second solution, cleaning it with deionized water, and drying it at a temperature of 25-50°C.

[0016] In a second aspect, the present invention provides a micro-arc oxidation film, which is prepared according to the above-mentioned method for preparing a micro-arc oxidation film with high hardness and low roughness for an annular aluminum part.

[0017] Compared with the prior art, the beneficial effects of the micro-arc oxidation film of the present invention are the same as the beneficial effects of the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part described in the above technical solution, and will not be repeated here. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.

[0020] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.

[0021] One of the rules of conventional micro-arc oxidation treatment is that with the increase of treatment time and voltage, the thickness, hardness and roughness of the ceramic film gradually increase. For annular aluminum alloy parts, affected by the charge skin effect, the growth rate of the film layer on the outer surface is much higher than that on the inner surface during the micro-arc oxidation process, resulting in uneven thickness of the inner and outer surfaces, and the micro-arc oxidation film formed has low hardness and excessive roughness, which seriously affects the performance of the annular aluminum alloy parts.

[0022] In order to solve the above technical problems, in a first aspect, the present invention provides a method for preparing a micro-arc oxidation film with high hardness and low roughness on an annular aluminum part, comprising: The annular aluminum piece is immersed in the first solution and the second solution in sequence, and then taken out and dried, so that a micro-arc oxidation film is formed on the surface of the annular aluminum piece; The first solution includes phosphate, silicate, EDTA salt, hydroxide and tartrate; the second solution includes hexametaphosphate, silicate, fluoride salt, EDTA salt, hydroxide and citrate.

[0023] Under the condition of adopting the above-mentioned technical scheme, the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention is used to prepare a micro-arc oxidation film on the inner and outer surfaces of the annular aluminum part, and the annular aluminum part is immersed in a first solution and a second solution in turn for micro-arc oxidation treatment. The annular aluminum part is immersed in the first solution for the first micro-arc oxidation treatment, and a first micro-arc oxidation reaction occurs during the first micro-arc oxidation treatment. The annular aluminum part is immersed in the second solution for the second micro-arc oxidation treatment, and a second micro-arc oxidation reaction occurs during the second micro-arc oxidation treatment. Specifically, in the process of the first micro-arc oxidation treatment, phosphate and silicate are used as the main salts in the first solution, which can enhance the passivation ability of the first solution on the annular aluminum part, and tartrate is used to exert the antioxidant effect of the first solution, thereby suppressing the excessively violent micro-arc oxidation reaction during the first micro-arc oxidation treatment. , and by controlling the parameters of the first micro-arc oxidation treatment within a reasonable range, a barrier layer can be formed on the surface of the annular aluminum part; in the process of the second micro-arc oxidation treatment, hexametaphosphate and silicate are used as the main salts to promote the growth effect of the film (such as uniformity, reasonable growth rate), and fluoride salts and hydroxides (high concentration) are added to increase the conductivity of the second solution, which is further used to enhance the micro-arc oxidation reaction; further, after the above-mentioned first micro-arc oxidation treatment, due to the strong passivation effect of the first solution, a high-density smooth micro-arc oxidation film can be quickly obtained on the surface of the annular aluminum part, but it is difficult to increase the thickness and hardness of the micro-arc oxidation film to the expected range. For this reason, the present invention selects a second solution with a strong ability to promote film growth during the second micro-arc oxidation treatment. After the second micro-arc oxidation treatment, the micro-arc oxidation film finally reaches the thickness requirement. The benefit is that in the first micro-arc oxidation treatment, the passivation layer (equivalent to the barrier layer, which plays a role in stimulating the second micro-arc oxidation reaction) is formed at a faster rate, and its density and smoothness are high; after the first micro-arc oxidation treatment, the passivation layer (or barrier layer) that has been formed on the surface of the annular aluminum part can directly stimulate the micro-arc oxidation reaction of the second micro-arc oxidation treatment. It is precisely because of the existence of the passivation layer that the uniformity of the second micro-arc oxidation reaction can be effectively improved, and the overall preparation time of the micro-arc oxidation film of the annular aluminum part can be shortened, which not only improves the preparation efficiency, but also ensures the high density and smoothness of the film layer (if the second micro-arc oxidation treatment is directly entered without the first micro-arc oxidation treatment, due to the weak passivation ability of the second solution, the passivation process will be slow, the treatment time will be greatly increased, and the roughness of the oxide film will increase and the density will decrease).Therefore, through the combined action (or mutual cooperation) of the first solution and the second solution, or in other words, through the combined action (or mutual cooperation) of the first micro-arc oxidation treatment and the second micro-arc oxidation treatment, the micro-arc oxidation film formed on the inner and outer surfaces of the annular aluminum part is maintained at a uniform level, and while the hardness of the micro-arc oxidation film is improved, the roughness of the micro-arc oxidation film can also be reduced, and a micro-arc oxidation film that meets the requirements is formed on the surface of the annular aluminum part. In summary, the above-mentioned technical solution of the present invention solves the technical problems that the thickness of the film layer on the inner and outer surfaces of the annular aluminum alloy part after the existing micro-arc oxidation treatment is uneven, and the formed micro-arc oxidation film has low hardness and excessive roughness, which seriously affects the performance of the annular aluminum alloy part.

[0024] It should be understood that in order to further improve the uniformity of the micro-arc oxidation film on the surface of the annular aluminum part, further improve the hardness and reduce the roughness, in the preparation method of the high-hardness and low-roughness micro-arc oxidation film for the annular aluminum part of the present invention, the content of each component in the first solution and the second solution should also be controlled within a reasonable range; for example, based on the amount of the first solution, the first solution includes 10-20 g / L of phosphate, 15-30 g / L of silicate, 3-8 g / L of EDTA salt, 0.5-3 g / L of hydroxide and 7~15g / L of tartrate. As another example, based on the dosage of the first solution, the phosphate content in the first solution can be 10g / L, 15g / L or 20g / L, the silicate content can be 15g / L, 20g / L or 30g / L, the EDTA content can be 3g / L, 5g / L or 8g / L, the hydroxide content can be 0.5g / L, 1.5g / L or 3g / L, and the tartrate content can be 7g / L, 11g / L or 15g / L. For example, based on the amount of the second solution, the second solution includes 15-25 g / L of hexametaphosphate, 15-30 g / L of silicate, 10-22 g / L of fluoride, 3-8 g / L of EDTA, 2-6 g / L of hydroxide and 5-10 g / L of citrate; for another example, based on the amount of the second solution, the content of hexametaphosphate in the second solution can be 15 g / L, 20 g / L or 25 g / L, the content of silicate can be 15 g / L, 20 g / L or 30 g / L, the content of fluoride can be 10 g / L, 15 g / L or 22 g / L, the content of EDTA can be 3 g / L, 5 g / L or 8 g / L, the content of hydroxide can be 2 g / L, 4 g / L or 6 g / L, and the content of citrate can be 5 g / L, 8 g / L or 10 g / L.

[0025] It should also be understood that in order to further improve the uniformity of the micro-arc oxidation film on the surface of the annular aluminum part, and further improve the hardness and reduce the roughness, in the preparation method of the high-hardness and low-roughness micro-arc oxidation film for annular aluminum parts of the present invention, the types of the components in the first solution and the second solution should also be controlled, that is, the types of phosphates, silicates, EDTA salts, hydroxides, tartrates, hexametaphosphates, fluoride salts and citrates; for example, the phosphates include trisodium phosphate and tripotassium phosphate, the silicates include sodium silicate and potassium silicate, the EDTA salts include disodium EDTA and dipotassium EDTA, the hydroxides include sodium hydroxide and potassium hydroxide, and the tartrates include tartrates. The phosphate may be trisodium phosphate or tripotassium phosphate, the silicate may be sodium silicate or potassium silicate, the EDTA salt may be disodium EDTA or dipotassium EDTA, the hydroxide may be sodium hydroxide or potassium hydroxide, the tartrate may be sodium tartrate, potassium tartrate or sodium potassium tartrate, the hexametaphosphate may be sodium hexametaphosphate, the fluoride salt may be sodium fluoride or potassium fluoride, and the citrate may be sodium citrate or potassium citrate.

[0026] It should also be understood that in order to further improve the uniformity of the micro-arc oxidation film on the surface of the annular aluminum part, and further improve the hardness and reduce the roughness, in the preparation method of the high-hardness and low-roughness micro-arc oxidation film for annular aluminum parts of the present invention, the temperature of the first solution and the second solution, as well as the current parameters of the first solution and the second solution should also be controlled within a reasonable range; for example, the temperature of the first solution and the second solution is 8~35°C, and the current parameters of the first solution include: frequency of 300~500Hz, duty cycle of 2.5~5%, current density of 1~2A / dm 2 , the termination voltage is 420-480V, and the treatment time is 8-15min, and the current parameters of the second solution include: frequency is 500-1000Hz, duty cycle is 4-12%, and current density is 1.5-5A / dm 2 , the termination voltage is 450-580V, and the treatment time is 20-35min; in another example, the temperature of the first solution and the second solution can be 8°C, 20°C or 35°C, and the current parameters of the first solution include a frequency of 300Hz, 400Hz or 500Hz, a duty cycle of 2.5%, 4% or 5%, and a current density of 1A / dm 2 , 1.5A / dm 2 or 2A / dm 2The termination voltage may be 420V, 450V or 480V, the treatment time may be 8min, 12min or 15min, the current parameters of the second solution may include a frequency of 500Hz, 800Hz or 1000Hz, a duty cycle of 4%, 8% or 12%, and a current density of 1.5A / dm 2 、3A / dm 2 or 5A / dm 2 The termination voltage can be 450V, 500V or 580V, and the processing time can be 20min, 30min or 35min.

[0027] As a possible implementation mode, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention, in the process of immersing the annular aluminum part in the first solution and the second solution in turn, the annular aluminum part is the anode, the stainless steel plate is the cathode, and an auxiliary cathode is provided.

[0028] In the case of adopting the above-mentioned technical scheme, the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention determines the anode and cathode in the process of preparing the micro-arc oxidation film, and sets an auxiliary cathode, wherein the annular aluminum part to be treated with micro-arc oxidation is the anode, and the stainless steel plate is the cathode; in the above-mentioned process, the setting of the auxiliary cathode can effectively eliminate the charge skin phenomenon caused by the annular structure, so that the growth rate of the oxide film on the inner and outer walls of the annular structure is more consistent, further improve the uniformity of the micro-arc oxidation film on the surface of the annular aluminum part, and further improve the hardness of the micro-arc oxidation film and reduce the roughness; that is, the setting of the auxiliary cathode further improves the performance of the annular aluminum part. By way of example, the auxiliary cathode includes a stainless steel tube, and the auxiliary cathode passes through the inner cavity of the annular aluminum part and does not contact the annular aluminum part; in another example, the auxiliary cathode is a stainless steel tube; Furthermore, in order to allow the auxiliary cathode to pass through the inner cavity of the annular aluminum part and ensure that the annular aluminum part after micro-arc oxidation treatment has excellent performance, the auxiliary cathode should also be controlled to have reasonable specifications relative to the annular aluminum part. For example, the diameter of the auxiliary cathode can be less than or equal to 1 / 2 of the minimum diameter of the inner cavity of the annular aluminum part, and the length of the auxiliary cathode can be less than or equal to 2 times the axial length of the annular aluminum part; for another example, the auxiliary cathode is a stainless steel tube, the diameter of the stainless steel tube can be less than or equal to 1 / 2 of the minimum diameter of the inner cavity of the annular aluminum part, and the length of the stainless steel tube can be less than or equal to 2 times the axial length of the annular aluminum part.

[0029] As a possible implementation mode, in the method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part of the present invention, the annular aluminum part is immersed in the first solution and the second solution in sequence, and then taken out and dried, comprising: Step 1, clamping the annular aluminum piece with a conductive hanger as an anode, the stainless steel plate as a cathode, passing the stainless steel tube through the inner cavity of the annular aluminum piece, and using the stainless steel tube as an auxiliary cathode; Step 2, immersing the annular aluminum part in the first solution and performing a first micro-arc oxidation treatment, wherein the first micro-arc oxidation treatment lasts for 8 to 15 minutes; Step 3, taking out the annular aluminum piece from the first solution and cleaning it with deionized water; Step 4, the annular aluminum piece is clamped with a conductive hanger as an anode, the stainless steel plate and the stainless steel tube are used as a cathode and an auxiliary cathode respectively, the annular aluminum piece is immersed in the second solution, and a second micro-arc oxidation treatment is performed, and the time of the second micro-arc oxidation treatment is 20 to 35 minutes; Step 5, taking out the annular aluminum piece from the second solution, cleaning it with deionized water, and drying it at a temperature of 25-50°C.

[0030] In the case of adopting the above technical scheme, the method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention is used to prepare a micro-arc oxidation film on the outer surface of the annular aluminum part, and the annular aluminum part is subjected to a first micro-arc oxidation treatment and a second micro-arc oxidation treatment respectively. During the first micro-arc oxidation treatment, phosphate and silicate are used as main salts in the first solution to enhance the passivation ability of the first solution on the annular aluminum part, and tartrate is used to exert the antioxidant effect of the first solution, thereby inhibiting the excessively violent micro-arc oxidation reaction during the first micro-arc oxidation treatment, and controlling the first micro-arc oxidation reaction. When the parameters of the micro-arc oxidation treatment are within a reasonable range, a barrier layer can be formed on the surface of the annular aluminum part; during the second micro-arc oxidation treatment, hexametaphosphate and silicate are used as main salts to promote the growth effect of the film (such as uniformity and reasonable growth rate), and fluoride salts and hydroxides (high concentration) are added to improve the conductivity of the second solution, which is further used to enhance the micro-arc oxidation reaction; further, the present invention adds citrate to the second solution, and the citrate plays a role in smoothing the oxide film during the second micro-arc oxidation treatment, so that the film layer can be rapidly thickened while suppressing the increase or improvement of the roughness of the film layer. Furthermore, in the present invention, an auxiliary cathode is provided during the first micro-arc oxidation treatment and the second micro-arc oxidation treatment of the annular aluminum part. The provision of the auxiliary cathode can effectively eliminate the charge skin phenomenon caused by the annular structure, so that the growth rate of the oxide film on the inner and outer walls of the annular structure is more consistent, further improving the uniformity of the micro-arc oxidation film on the surface of the annular aluminum part, and further improving the hardness and reducing the roughness of the micro-arc oxidation film, thereby further improving the performance of the annular aluminum part. By way of example, the auxiliary cathode can be a stainless steel tube, the time for the first micro-arc oxidation treatment can be 8 minutes, 12 minutes or 15 minutes, the time for the second micro-arc oxidation treatment can be 20 minutes, 30 minutes or 35 minutes, and the drying temperature can be 25°C, 30°C or 50°C. It should be noted that in order to smoothly form a stable barrier layer on the annular aluminum part during the first micro-arc oxidation treatment, the annular aluminum part needs to be surface treated. By way of example, before the first micro-arc oxidation treatment, the annular aluminum part can be degreased, the surface oxide film removed, washed with water and dried in sequence.

[0031] In a second aspect, the present invention provides a micro-arc oxidation film, which is prepared by the method for preparing the high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part of the present invention.

[0032] When this technical solution is adopted, the micro-arc oxidation film is formed on the surface of the annular aluminum part, has a high degree of uniformity, and has the characteristics of low roughness and high hardness; for example, on the inner wall of the annular aluminum part, the hardness of the micro-arc oxidation film is 800~1500HV, the thickness is 10~20μm, and the roughness is 1.2~2.0Ra; on the outer wall of the annular aluminum part, the hardness of the micro-arc oxidation film is 1000~1800HV, the thickness is 12~25μm, and the roughness is 1.5~2.5Ra.

[0033] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.

[0034] Unless otherwise specified, the raw materials used in the following examples are commercially available. Example 1

[0035] This embodiment provides a method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part, comprising: S100, preparing 100 L of the first solution and the second solution with deionized water; The contents of the components in the first solution are: 20 g / L of tripotassium phosphate, 20 g / L of potassium silicate, 8 g / L of dipotassium EDTA, 1.5 g / L of sodium hydroxide and 12 g / L of potassium sodium tartrate; The contents of the components in the second solution are: 21 g / L sodium hexametaphosphate, 20 g / L potassium silicate, 15 g / L potassium fluoride, 4 g / L dipotassium EDTA, 5 g / L potassium hydroxide, and 8 g / L sodium citrate; S200, obtaining an annular aluminum part (i.e., an annular aluminum alloy sample), wherein the inner diameter of the annular aluminum part is 8 cm and the outer diameter is 8.6 cm; S300, fixing the stainless steel tube auxiliary cathode vertically upward at the bottom of the micro-arc oxidation tank, connecting it to the cathode of the micro-arc oxidation power supply, and completely immersing it in the first solution; S400, clamp the annular aluminum piece with a universal conductive hanger and connect it to the anode of the micro-arc oxidation power supply. The annular cavity of the annular aluminum piece passes through the stainless steel tube and is immersed in the first solution vertically at the liquid surface. Turn on the micro-arc oxidation solution circulation cooling device, and the cooling target is set to 25°C; S500, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 350Hz, the duty cycle to 4%, the current density to 1.2A / dm2, set the termination voltage to 450V, the processing time to 10min, and the equipment automatically stops working when the termination conditions are met; S600, take out the hanger together with the annular aluminum part and clean it with deionized water, and replace the first solution in the micro-arc oxidation tank with the second solution; S700, immersing the annular aluminum piece held by the hanger vertically into the second solution in such a manner that the annular cavity passes through the stainless steel tube; S800, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 600Hz, the duty cycle to 6%, the current density to 3.8A / dm2, set the termination voltage to 540V, the processing time to 30min, and the equipment automatically stops working when the termination conditions are met; S900, taking out the annular aluminum part, cleaning it with deionized water and drying it at a drying temperature of 25° C., and obtaining a micro-arc oxidation film with low inner and outer surface roughness, uniform thickness and high hardness of the annular aluminum part. Example 2

[0036] This embodiment provides a method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part, comprising: S100, preparing 100 L of the first solution and the second solution with deionized water; The contents of the components in the first solution are: 15 g / L trisodium phosphate, 15 g / L sodium silicate, 6 g / L disodium EDTA, 1 g / L sodium hydroxide and 8 g / L potassium tartrate; The contents of the components in the second solution are: 18 g / L sodium hexametaphosphate, 16 g / L sodium silicate, 20 g / L potassium fluoride, 6 g / L disodium EDTA, 5 g / L sodium hydroxide and 8 g / L sodium citrate; S200, obtaining an annular aluminum part (i.e., an annular aluminum alloy sample), the inner diameter of the annular aluminum part is 6 cm, and the outer diameter is 7.5 cm, and the annular aluminum part is subjected to degreasing, surface oxide film removal, water washing, and drying treatments; S300, fixing the stainless steel tube auxiliary cathode vertically upward at the bottom of the micro-arc oxidation tank, connecting it to the cathode of the micro-arc oxidation power supply, and completely immersing it in the first solution; S400, clamp the annular aluminum piece with a universal conductive hanger and connect it to the anode of the micro-arc oxidation power supply. The annular cavity of the annular aluminum piece passes through the stainless steel tube and is immersed in the first solution vertically at the liquid surface. Turn on the micro-arc oxidation solution circulation cooling device, and the cooling target is set to 25°C; S500, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 300Hz, the duty cycle to 5%, the current density to 1A / dm2, set the termination voltage to 450V, the processing time to 12min, and the equipment automatically stops working when the termination conditions are met; S600, take out the hanger together with the annular aluminum part and clean it with deionized water, and replace the first solution in the micro-arc oxidation tank with the second solution; S700, immersing the annular aluminum piece held by the hanger vertically into the second solution in such a manner that the annular cavity passes through the stainless steel tube; S800, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 650Hz, the duty cycle to 7%, the current density to 4.5A / dm2, set the termination voltage to 540V, the processing time to 26min, and the equipment automatically stops working when the termination conditions are met; S900, taking out the annular aluminum part, cleaning it with deionized water and drying it at a drying temperature of 30° C., and obtaining a micro-arc oxidation film with low inner and outer surface roughness, uniform thickness and high hardness of the annular aluminum part. Example 3

[0037] This embodiment provides a method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part, comprising: S100, preparing 100 L of the first solution and the second solution with deionized water; The contents of the components in the first solution are: 16 g / L of tripotassium phosphate, 16 g / L of potassium silicate, 8 g / L of dipotassium EDTA, 1.5 g / L of sodium hydroxide and 12 g / L of potassium sodium tartrate; The contents of the components in the second solution are: 20 g / L sodium hexametaphosphate, 18 g / L potassium silicate, 15 g / L potassium fluoride, 5 g / L dipotassium EDTA, 3 g / L sodium hydroxide and 8 g / L sodium citrate; S200, obtaining an annular aluminum part (i.e., an annular aluminum alloy sample), the inner diameter of the annular aluminum part is 8 cm, and the outer diameter is 8.6 cm, and the annular aluminum part is subjected to degreasing, surface oxide film removal, water washing, and drying treatments; S300, fixing the stainless steel tube auxiliary cathode vertically upward at the bottom of the micro-arc oxidation tank, connecting it to the cathode of the micro-arc oxidation power supply, and completely immersing it in the first solution; S400, clamp the annular aluminum piece with a universal conductive hanger and connect it to the anode of the micro-arc oxidation power supply. The annular cavity of the annular aluminum piece passes through the stainless steel tube and is immersed in the first solution vertically at the liquid surface. Turn on the micro-arc oxidation solution circulation cooling device, and the cooling target is set to 25°C; S500, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 400Hz, the duty cycle to 4%, the current density to 1.5A / dm2, set the termination voltage to 480V, the processing time to 10min, and the equipment automatically stops working when the termination conditions are met; S600, take out the hanger together with the annular aluminum part and clean it with deionized water, and replace the first solution in the micro-arc oxidation tank with the second solution; S700, immersing the annular aluminum piece held by the hanger vertically into the second solution in such a manner that the annular cavity passes through the stainless steel tube; S800, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 550Hz, the duty cycle to 8%, the current density to 3.5A / dm2, set the termination voltage to 560V, the processing time to 35min, and the equipment automatically stops working when the termination conditions are met; S900, taking out the annular aluminum part, cleaning it with deionized water and drying it at a drying temperature of 50° C., and obtaining a micro-arc oxidation film with low inner and outer surface roughness, uniform thickness and high hardness of the annular aluminum part.

[0038] Comparative Example 1 This comparative example provides a method for preparing a high-hardness and low-roughness micro-arc oxidation film on an annular aluminum part. Compared with Example 1, this comparative example only performs the first micro-arc oxidation treatment on the annular aluminum part. The preparation method comprises: S100, preparing 100 L of the first solution and the second solution with deionized water; The contents of the components in the first solution are: 15 g / L trisodium phosphate, 15 g / L sodium silicate, 6 g / L disodium EDTA, 1 g / L sodium hydroxide and 8 g / L potassium tartrate; The contents of the components in the second solution are: 18 g / L sodium hexametaphosphate, 16 g / L sodium silicate, 20 g / L potassium fluoride, 6 g / L disodium EDTA, 5 g / L sodium hydroxide and 8 g / L sodium citrate; S200, obtaining an annular aluminum part (i.e., an annular aluminum alloy sample), the inner diameter of the annular aluminum part is 8 cm, and the outer diameter is 8.6 cm, and the annular aluminum part is subjected to degreasing, surface oxide film removal, water washing, and drying treatments; S300, fixing the stainless steel tube auxiliary cathode vertically upward at the bottom of the micro-arc oxidation tank, connecting it to the cathode of the micro-arc oxidation power supply, and completely immersing it in the first solution; S400, clamp the annular aluminum piece with a universal conductive hanger and connect it to the anode of the micro-arc oxidation power supply. The annular cavity of the annular aluminum piece passes through the stainless steel tube and is immersed in the first solution vertically at the liquid surface. Turn on the micro-arc oxidation solution circulation cooling device, and the cooling target is set to 25°C; S500, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 300Hz, the duty cycle to 5%, the current density to 1A / dm2, set the termination voltage to 450V, the processing time to 12min, and the equipment automatically stops working when the termination conditions are met; S600, take out the annular aluminum part, clean it with deionized water and dry it at a drying temperature of 25°C.

[0039] Comparative Example 2 This comparative example provides a method for preparing a micro-arc oxidation film with high hardness and low roughness on an annular aluminum part. Compared with Example 1, this comparative example does not provide an auxiliary cathode, that is, does not provide a stainless steel tube as an auxiliary cathode. The preparation method comprises: S100, preparing 100 L of the first solution and the second solution with deionized water; The contents of the components in the first solution are: 20 g / L of tripotassium phosphate, 20 g / L of potassium silicate, 8 g / L of dipotassium EDTA, 1.5 g / L of sodium hydroxide and 12 g / L of potassium sodium tartrate; The contents of the components in the second solution are: 21 g / L sodium hexametaphosphate, 20 g / L potassium silicate, 15 g / L potassium fluoride, 4 g / L dipotassium EDTA, 5 g / L potassium hydroxide, and 8 g / L sodium citrate; S200, obtaining an annular aluminum part (i.e., an annular aluminum alloy sample), wherein the inner diameter of the annular aluminum part is 6 cm and the outer diameter is 7.5 cm; S300, clamp the annular aluminum piece with a universal conductive hanger and connect it to the anode of the micro-arc oxidation power supply, immerse the annular aluminum piece vertically in the first solution, turn on the micro-arc oxidation solution circulation cooling device, and set the cooling target to 25°C; S400, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 350Hz, the duty cycle to 4%, the current density to 1.2A / dm2, set the termination voltage to 450V, the processing time to 10min, and the equipment automatically stops working when the termination conditions are met; S500, taking out the hanger together with the annular aluminum part and cleaning it, and replacing the first solution in the micro-arc oxidation tank with the second solution; S600, immersing the annular aluminum piece held by the hanger vertically into the second solution; S700, turn on the micro-arc oxidation power supply equipment, adjust the current frequency to 600Hz, the duty cycle to 6%, the current density to 3.8A / dm2, set the termination voltage to 540V, the processing time to 30min, and the equipment automatically stops working when the termination conditions are met; S800, taking out the annular aluminum part, cleaning it with deionized water and drying it at a drying temperature of 25° C., and obtaining a micro-arc oxidation film with low inner and outer surface roughness, uniform thickness and high hardness of the annular aluminum part.

[0040] According to the above-mentioned Examples 1 to 3, as well as Comparative Examples 1 and 2, after a micro-arc oxidation film is prepared on the surface of the annular aluminum part, the hardness of the micro-arc oxidation film is tested by a micro-Vickers hardness tester, the thickness of the micro-arc oxidation film is measured by a film thickness meter, and the roughness of the micro-arc oxidation film is measured by a roughness meter. The measurement or test results are detailed in Table 1 below.

[0041] Table 1 Measurement or test results of micro-arc oxidation films of embodiments and comparative examples

[0042] It can be seen from Table 1 above that, relative to Comparative Example 1 and Comparative Example 2, the micro-arc oxidation films on the inner and outer surfaces of the annular aluminum alloy parts prepared in Examples 1 to 3 above have the characteristics of high hardness, low roughness and uniform film thickness, indicating that the two-step micro-arc oxidation method provided by the present invention and the auxiliary cathode measures ensure the realization of the purpose of the present invention. Comparing the above-mentioned Comparative Examples 1 and 2 with the embodiments, it can be seen that the oxide film thickness and hardness prepared by single-step micro-arc oxidation in Comparative Example 1 are insufficient (the outer wall thickness is 15 μm, the inner wall thickness is 13 μm, the outer wall hardness is 665 HV, and the inner wall hardness is 602 HV), while the oxide film prepared by micro-arc oxidation without using an auxiliary cathode in Comparative Example 2 has high roughness and a large difference in inner and outer film thickness (the outer wall roughness is 3.5 Ra, the inner wall roughness is 1.9 Ra, the outer wall thickness is 25 μm, and the inner wall thickness is 15 μm), indicating that by using electrolytic solutions of different formulations (the first solution and the second solution) for two-step micro-arc oxidation treatment and providing an auxiliary cathode (such as the above-mentioned stainless steel tube), a micro-arc oxidation film (i.e., a micro-arc oxidation ceramic film) with uniform thickness, high hardness and low roughness can be prepared on the surface of the annular aluminum part.

[0043] In the description of the above embodiments, specific features, structures, materials or characteristics may be combined in a suitable manner in any one or more embodiments or examples.

[0044] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part, characterized in that: include: The annular aluminum piece is immersed in the first solution and the second solution in sequence, and then taken out and dried, so that a micro-arc oxidation film is formed on the surface of the annular aluminum piece; The first solution includes phosphate, silicate, EDTA salt, hydroxide and tartrate; the second solution includes hexametaphosphate, silicate, fluoride salt, EDTA salt, hydroxide and citrate.

2. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 1, characterized in that: In terms of the amount of the first solution, the first solution includes 10-20 g / L of phosphate, 15-30 g / L of silicate, 3-8 g / L of EDTA salt, 0.5-3 g / L of hydroxide and 7-15 g / L of tartrate; and / or, In terms of the amount of the second solution, the second solution includes 15-25 g / L of hexametaphosphate, 15-30 g / L of silicate, 10-22 g / L of fluoride salt, 3-8 g / L of EDTA salt, 2-6 g / L of hydroxide and 5-10 g / L of citrate.

3. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 2, characterized in that: The phosphate includes trisodium phosphate and tripotassium phosphate; and / or, The silicate comprises sodium silicate and potassium silicate; and / or, The EDTA salt includes disodium EDTA and dipotassium EDTA; and / or, The hydroxide comprises sodium hydroxide and potassium hydroxide; and / or, The tartrate includes sodium tartrate, potassium tartrate and sodium potassium tartrate; and / or, The hexametaphosphate includes sodium hexametaphosphate; and / or, The fluoride salts include sodium fluoride and potassium fluoride; and / or, The citrate includes sodium citrate and potassium citrate.

4. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 3, characterized in that: In the process of immersing the annular aluminum member in the first solution and the second solution in sequence, the temperature of the first solution and / or the second solution is 8-35°C.

5. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 4, characterized in that: In the process of immersing the annular aluminum piece in the first solution and the second solution in sequence, the current parameters of the first solution include: a frequency of 300-500 Hz, a duty cycle of 2.5-5%, and a current density of 1-2 A / dm 2 , the termination voltage is 420~480V, and the processing time is 8~15min; and / or, The current parameters of the second solution include: frequency of 500-1000 Hz, duty cycle of 4-12%, current density of 1.5-5 A / dm 2 , the termination voltage is 450~580V, and the processing time is 20~35min.

6. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 5, characterized in that: In the process of immersing the annular aluminum piece in the first solution and the second solution in sequence, the annular aluminum piece is used as the anode, the stainless steel plate is used as the cathode, and an auxiliary cathode is provided.

7. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 6, characterized in that: The auxiliary cathode comprises a stainless steel tube; and / or, During the process of immersing the annular aluminum member in the first solution and the second solution in sequence, the auxiliary cathode passes through the inner cavity of the annular aluminum member.

8. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 7, characterized in that: The diameter of the auxiliary cathode is less than or equal to 1 / 2 of the minimum diameter of the inner cavity of the annular aluminum part; and / or, The length of the auxiliary cathode is less than or equal to twice the axial length of the annular aluminum member.

9. The method for preparing a high-hardness and low-roughness micro-arc oxidation film for an annular aluminum part according to claim 8, characterized in that: The method of immersing the annular aluminum piece in the first solution and the second solution in sequence and then taking it out to dry comprises: Step 1, clamping the annular aluminum piece with a conductive hanger as an anode, the stainless steel plate as a cathode, passing the stainless steel tube through the inner cavity of the annular aluminum piece, and using the stainless steel tube as an auxiliary cathode; Step 2, immersing the annular aluminum part in the first solution and performing a first micro-arc oxidation treatment, wherein the first micro-arc oxidation treatment lasts for 8 to 15 minutes; Step 3, taking out the annular aluminum piece from the first solution and cleaning it with deionized water; Step 4, the annular aluminum piece is clamped with a conductive hanger as an anode, the stainless steel plate and the stainless steel tube are used as a cathode and an auxiliary cathode respectively, the annular aluminum piece is immersed in the second solution, and a second micro-arc oxidation treatment is performed, and the time of the second micro-arc oxidation treatment is 20 to 35 minutes; Step 5, taking out the annular aluminum piece from the second solution, cleaning it with deionized water, and drying it at a temperature of 25-50°C.

10. A micro-arc oxidation film, characterized in that: The high-hardness and low-roughness micro-arc oxidation film of an annular aluminum part is prepared according to the method for preparing the high-hardness and low-roughness micro-arc oxidation film of any one of claims 1 to 9.

Citation Information

Cited By

  • Prefabricated branch fireproof cable with copper metal shell and preparation method of prefabricated branch fireproof cable

    CN121191833A